Water Balance Supporting the Irrigation Water Demand in Java Island, Indonesia - Yudha Mediawan; Lily Montarcih; Widandi Soetopoi; Tri Budi Prayogo (Indonesian Journal of Geography, 2021)
Java is the most populous island with the largest percentage of rice fields in Indonesia. However, rice fields in Java Island often experience water shortages, so an analysis of the potential water availability for irrigation in Java is required. This research aims to analyze water's potential to meet irrigation water needs in each catchment area in Java. In this research, the potential for irrigation water in Java is calculated based on the balance of water balance between water availability and DMI and Irrigation water needs. This research is divided into two parts: (1) analysis of water availability using the WFLOW hydrological simulation; and (2) water demand analysis based on population statistical data. Based on this research, it can be concluded that the water balance between water resources and irrigation water needs in Java is still in the surplus category, even though there are deficits in several catchment areas (WS): in the Kepulauan Seribu, Wiso Gelis, and Welang Rejoso WS. WS with the most water availability is generally located in wide (WS) areas, while several WS with abundant water needs is generally located in WS with the densest population. According to The Central Bureau of Statistics (BPS), the agricultural area in Java has decreased by an average of 20 thousand hectares per year, so that the demand for irrigation water on the island of Java will also decrease. Consequently, the excess water potential in Java Island needs to be allocated to meet the needs of DMI, which are increasing every year. In addition, the results also show that the development of irrigation areas in the future should be focused on large (WS) areas that have the potential for significant amounts of irrigation water.